The Proliferation and Migration-Enhancing Effects of Vitronectin in SMMC 7721 Cells: A Pilot Study - Wei Zhu; Konghe Hu; WenXue Li; Guangyu Yang; Jianling Chen; Chuanxi Fu; Qiansheng Hu (Journal of Basic & Applied Sciences, 2014)
To understand the effects of Vitronectin on cell proliferation and migration in the cell line of hepatocellular carcinoma, SMMC 7721, the effects of Vitronectin on cell proliferation rate or on the prevention of the cells from the apoptotic stimuli were appraised with WST-1 assay; and the morphology of b-Tubulin was observed with con-focal microscope. The effect on migration was detected with transwell chamber. The results show that Vitronectin helps the cells adhere to Petri dish as well as the sustaining of the morphology of b-Tubulin. Vitronectin could enhance the proliferation rate of SMMC 7721 with the concentration-effect mode, and could protect the cells from the stimuli of apoptosis inducer. As to cell migration, the results show that Vitronectin enhance cell migration across the membrane of transwell chamber. According the results, the conclusion could be made that Vitronectin might play important roles in the following biological effects, such as sustaining the morphology of the tumor cells, enhancing the proliferation as well as the migration.